2011
DOI: 10.1016/j.bpc.2011.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of a two-transmembrane-helix peptide with lipid bilayers and dodecyl sulfate micelles

Abstract: To probe structural changes that occur when a membrane protein is transferred from lipid bilayers to SDS micelles, a fragment of bacteriorhodopsin containing transmembrane helical segments A and B was studied by fluorescence spectroscopy, molecular dynamics (MD) simulation, and stopped flow kinetics. In lipid bilayers, Förster resonance energy transfer (FRET) was observed between tyrosine 57 on helix B and tryptophans 10 and 12 on helix A. FRET efficiency decreased substantially when the peptide was transferre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…To investigate the structural changes in the transmembrane part that occur upon transfer from the lipid membrane to SDS micelle environment, a two helix fragment comprising transmembrane helix A and B of bR was recently investigated by FRET [89]. The protein intrinsic tryptophan (helix A) and tyrosine (helix B) residues were utilized.…”
Section: Experimental Approaches To Gain Unique Insight Into Rhodomentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate the structural changes in the transmembrane part that occur upon transfer from the lipid membrane to SDS micelle environment, a two helix fragment comprising transmembrane helix A and B of bR was recently investigated by FRET [89]. The protein intrinsic tryptophan (helix A) and tyrosine (helix B) residues were utilized.…”
Section: Experimental Approaches To Gain Unique Insight Into Rhodomentioning
confidence: 99%
“…The protein intrinsic tryptophan (helix A) and tyrosine (helix B) residues were utilized. Importantly, the study indicated that disappearance of FRET upon changing the environment does not necessarily indicate structural disruption, but may also be explained by changes in the photophysics of the fluorophores [89]. …”
Section: Experimental Approaches To Gain Unique Insight Into Rhodomentioning
confidence: 99%
“…Therefore, to understand the peptides conformational changes, inter- or intramolecular interactions, the CD analyses were performed in specific solvents. SDS was used to simulate peptide-membrane interactions, simulating natural biological environments [ 25 ]; TFE induce an α-helix formation and stabilize the secondary structure [ 26 ]; MeOH promotes β-turns conformation The results suggest that all peptides, except peptide 3, tend to adopt β-turns conformation (Fig. 1 ) [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…In a similar unfolding study, two TM helices of bacteriorhodopsin that are known to associate (helices A and B) were transferred from 1,2‐dioleoylphosphatidylcholine (DOPC) bilayers to SDS micelles . This study involved the use of intrinsic FRET from a tyrosine on one peptide to two tryptophan residues on the other peptide.…”
Section: Fret Studies Of Tm Interactions In Lipid and Detergentmentioning
confidence: 99%